Analisis Preferensi Konsumen terhadap Produk Gula Aren Di Kecamatan Awayan Kabupaten Balangan - Yudhi Harianto; Nurul Wahdah (Rawa Sains: Jurnal Sains STIPER Amuntai, 2017)
This study aims to examine the attributes of palm sugar which is the preference or preference of consumers in making decisions to purchase palm sugar in traditional markets in the District of Awayan, Balangan Regency. This research was conducted in traditional markets in Awayan District, Balangan Regency, namely Awayan Market and Bihara Market. The basic method of research used is a qualitative descriptive method and the method of data collection using the interview method. Data collection was carried out from May to August 2017. Determination of the study sample using lottery simple random sampling method with a sample size of 50 people. The types of data used are primary data and secondary data. The analytical tool used is Chi-Square analysis. The results of the Chi-Square analysis showed that all variables of palm sugar were significantly different at the 95% confidence level. This means that consumer preference for palm sugar in traditional markets in Awayan District, Balangan Regency is not the same or there are differences in consumer preferences for palm sugar and all attributes included in consumer preferences. Palm sugar which is the preference of consumers in the traditional market of Awayan Subdistrict, Balangan Regency is palm sugar which has a brown color, sweet taste, medium size, plastic packaging and prices range from Rp. 16,000.00 - Rp. 18,000.00 per kg.